IDENTIFICATION OF BIRD SOUND AS THE TOOLS FOR ENVIRONMENTAL QUALITY MONITORING IN GREEN OPEN SPACE - Inggita Utami; Danni Setyawan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
The presence of a bird community can be used as a bioindicator of environmental quality in suburban areas. Bird identification from sound recording has developed in the last decade. This research aims to analyze the quality of green open space in the suburban area of Sleman Regency based on bird acoustic analysis. Data collection was carried out from November 2020 to March 2021 on river borders and city parks. Bird sound data was carried out using a mobile phone, facilitated by the Arbimon Touch application, in the morning, afternoon, and evening at intervals of five minutes on and ten minutes off for five days. The sound recordings and spectrograms were identified and validated through the database on the xeno-canto website. The identified birds are then used to calculate the Bird Community Index (BCI). The analysis of sound recordings found 29 bird species from 18 families in the sampling location. In addition, four birds were recorded as vulnerable or protected. The Progo River Border is the green open space with the highest species number of birds, but the Kayen river border and the Taman Keanekaragaman Hayati dan Arboretum Bambu have the best environmental quality to the presence of the higher specialist bird. Based on the bird community index, the environmental quality of the GOS in the suburban area of Sleman Regency has a moderate to very low level of environmental quality due to the low presence of specialist birds.